STUDI MENGENAI ORIENTASI INOVASI, PENGEMBANGAN PRODUK DAN EFEKTIFITAS PROMOSI SEBAGAI SEBUAH STRATEGI UNTUK MENINGKATKAN KINERJA PRODUK - Farida Indriani (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
ABSTRACT Dynamic of business environment nowadays has forced companies to develop their business performance, especially product performance. Due to increase in product innovation and product development, product performance will then also increase. Series of activities done by companies affecting product performance can be done by way of the quality of relationship with customers, where those activities are intended to support product performance. The high quality of relationship can be achieved only when there are strong commitment and high trust of customers toward the sellers. Keywords: Innovation; Product Development; Promotion; Product Performance